PANCASILA SEBAGAI WUJUD ISLAM RAHMATAN LI AL-ALAMIIN - Hosaini, Hosaini; Fikro, Muhammad Ihyaul (Asosiasi Dosen PTKIS Indonesia, 2021)
Abstract: Talks about governance in Islam and the relationship between the state and religion have never ended. Raising the wealth of Muslim ijtihad in examining the intellectual foundation of the role of the state and government in an Islamic way. The polemic that finally appears to be a problem of ijtihadiyah. Often, questions arise about the content of Islamic philosophical values ​​in the formation of the Republic of Indonesia. Therefore this article examines the construction of the Republic of Indonesia in the view of Maqasid Syariah. This study uses the Maqasid Sharia theory, which is to examine the deepest intentions of the formation of the Republic of Indonesia and its components, regarding Pancasila, Pancasila Democracy, the 1945 Constitution and the Presidential Government System. This study proposes the finding that Pancasila contains the meaning that prioritizes the maintenance of religion, then integrates it with other al-kulliyat al-khamsah. Furthermore, Pancasila Democracy is present as a diversification of the path of democratic politics. Keywords: Pancasila, Islam Rahmatan li al-Alamiin, Maqhosidal-Syari'ah.